SEROTYPE IDENTIFICATION OF VIBRIO CHOLERAE ISOLATED FROM ICE THAT USE FOR MARINE PRODUCT PRESERVATIVE BETWEEN MODERN AND TRADITIONAL MARKET IN DENPASAR - I P Ananta WS; IGM Wijaya P; IGP Dhinarananta; P Yuniadi A; M Agus Hendrayana (E-Jurnal Medika Udayana, 2013)
Colera is a disease that cause by Vibrio cholerae (V. cholerae). V. cholerae ) is one of pathogen bacteria that can be gained from contaminated dietary sources. However, Indonesian people having indulgence in consuming seafood. They usually acquire the marine products at the nearby market. In the other side, unhygienic process in provision of raw materials possibly increase the contamination of V. cholerae. The purpose of this study are to obtain the contamination of V. cholerae on the marine products in Denpasar. This study using observational descriptive method with quotas sampling by taking fish ice preservative used by fish merchants in the modern market and traditional markets as the samples. Six samples taken in each location (traditional and modern market). Sample then cultured with medium alkaline peptone water ( APW ) continued with thiosulfate citrate bile salt sucrose ( TCBS ). The result of the TCBS culture then continued by undergo grams staining and latex serotyping procedure to identify type V. vholerae. Every samples then noted and compared. The result on samples of modern market found 5 from 6 samples ( 83,33 % ) positive contains V. cholerae with Inaba serotype. Samples of traditional market found 4 from 6 sample (66,67%) positive contains V. cholerae with inaba serotype and 1 of them (16,67%) with Hikojima serotype. This study represent that contamination of V. cholerae are still high and potentially endanger people of Denpasar.